ISOLEUCINE EPIMERIZATION AND AMINO ACID COMPOSITION IN MOLECULAR-WEIGHT SEPARATIONS OF PLEISTOCENE GENYORNIS EGGSHELL - Kaufman D.S.; Miller G.H. (My University, 1995)
This study explores the geochronological utility and analytical reproducibility of separating the high-molecular-weight fraction (HMW) from eggshells of the extinct late Pleistocene ratite, Genyornis, using disposable, prepacked gel-filtration columns. The superior integrity of ratite eggshell for the retention of amino acids indicates that this biomineral is better suited for this type of investigation than previously studied molluscan shell. To evaluate the reproducibility of the gel-filtration technique, we analyzed triplicate subsamples of three eggshells of different ages. The reproducibility, based on the average intrashell variation (coefficient of variation; CV) in the extent of isoleucine epimerization (alle/Ile) in the HMW (enriched in molecules ca. >10,000 MW) is 3%, well within the range appropriate for geochronological purposes. The average intrashell variation in the total amino acid concentration (Σ[aa]) of the HMW is 5%, somewhat better than for the total acid hydrolysate (Total) of the same samples (7%). To evaluate the relation between molecular weight and the rate of isoleucine epimerization, three molecular-weight fractions were separated using gel filtration, plus the naturally hydrolyzed free fraction (Free), for each of four fossil eggshells. AIle/Ile increases with decreasing molecular weight in all shells, with a ca. sixfold to ninefold difference in ratios between the HMW and Free, and a ca. fivefold difference between the HMW and Total. Although linear correlations between aIle/Ile measured in each molecular-weight fraction and in the Total are all highly significant (r =< 0.951), the relation between the extent of epimerization in the HMW and in the Total is best expressed as an exponential function (r = 0.951). This relation is consistent with the idea that, as the epimerization reaction approaches equilibrium in the Total (ca. aIle/Ile > 1.1), its rate decreases beyond that of the HMW. The amino acid composition (relative percent of eight amino acids or combinations of amino acids) is more uniform in the HMW of the four samples compared to lower-molecular-weight fractions. The greater ''compositional stability'' of the HMW indicates that it contains a residuum of macromolecules that have not been affected by the diagenetically driven changes observed in lower-molecular-weight fractions.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен